Trysee - John Anderson (1841)
This diagram represents a plan of part of Trysee in the parish of St. Ann containing 188 acres and 32 perches, now subdivided as per the desire of John Anderson.
Keywords: Programme. -- Jamaica; Trysee, St. Ann. -- Jamaica